write the quadratic expression whose roots are 2 and -6 and whose leading coefficients is 3.
use the letter x to represent the variable.
y = 3 (x-2) (x+6)
Please let me know if you have any questions and best me if you are satisfactory.
3 (x-2) (x+6) = 0
3(x^2+4x-12) = 0
3x^2+12x-36 = 0
ok thank you for breaking that down clearer!
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?